Respuesta :

Answer: Solution for 6-8x=-5x+6 equation:

6-8x=-5x+6

We move all terms to the left:

6-8x-(-5x+6)=0

We get rid of parentheses

-8x+5x-6+6=0

We add all the numbers together, and all the variables

-3x=0

x=0/-3

x=0

Step-by-step explanation:

Answer:

1. Given

2. Addition Property of Equality

3. Simplify

4. Subtraction Property of Equality

5. Simplify

6. Division Property of Equality

7. Simplify

8. Answer

Step-by-step explanation:

1. Given

2. Addition Property of Equality

3. Simplify

4. Subtraction Property of Equality

5. Simplify

6. Division Property of Equality

7. Simplify

8. Answer